Synthesis and Characterization of Ag+ ,Pb+2 ,Fe+3 ,Cr+3 Complexes with the New Antipyrene – Azo Ligand. - Al-Hasani, T.J.; Al-witry, Z.A.; Hashim, R.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
oupling reaction of 4-aminoantipyrene with the (L-Histidine) gave the new bidentate azo ligand.The prepared ligand was identified by FT.IR, UV-Vis and HNMR spectroscopics technique. Treatment of the prepared ligand was done with the following metal ions (Ag+ ,Pb+2 ,Fe+3 ,Cr+3  ) in aqueous ethanol with a1:1 and 1:2  M:L ratio . The prepared complexes were characterized by using FT. IR and UV- VIS spectroscopic method as well as conductivity measurements. Their structures were suggested according to the results obtained.